ANALYSIS OF DETERMINANT FACTORS TOWARD MARGIN MURABAHAH OF INDONESIA ISLAMIC BANKS - PURWANTO PURWANTO; SOPHIA DWI RATNA (Journal of Business Studies and Management Review, 2018)
This research was conducted to find out the effect of the internal and external factors toward margin murabahah at syariah banks for period 2011-2016. The type of data used in this research is secondary data of Islamic Banks publish in quarterly financial statements by Otoritas Jasa Keuangan (OJK). Through purposive sampling, this research got 54 observations from three Islamic banks in five years which fulfill the criteria. This research used quantative approach, using multiple regression and has passed the classical assumption test. Based on the result, it is concluded that there are 4 independent variables which areThird Party Funds, Operational Efficiency Ratio, Non-Performing Financing, and Inflation which having significant effects toward margin murabahah. Simultaneously, the variation of four independent variables can explain 63.81% effects to dependent variable. The remaining of 36.19% is explained by other factors outside this research.